Efficacy of Acamprosate for Alcohol Dependence in a Family Medicine Setting in the United States: A Randomized, Double‐Blind, Placebo‐Controlled Study. (7th November 2012) - Berger, Lisa; Fisher, Michael; Brondino, Michael; Bohn, Michael; Gwyther, Robert; Longo, Lance; Beier, Nicole; Ford, Amy; Greco, Joe; Garbutt, James C.
<x xml:space="preserve">Abstract</x> Background Acamprosate has been found to enhance rates of complete abstinence and to increase percent days abstinent (PDA) from alcohol relative to placebo treatment. As most U.S. clinical trials of acamprosate have been conducted in alcohol and other drug specialty clinics, there is a need to examine the efficacy of acamprosate in generalist settings. This study tested the efficacy of acamprosate versus placebo on the primary study outcome of PDA in the treatment of alcohol‐dependent patients in a family medicine setting. Secondary study outcomes included percent heavy drinking days (%HDD) and gamma glutamyltransferase level (normal or high). Methods A randomized, double‐blind, placebo‐controlled, parallel group design of acamprosate was conducted in 2 family medicine settings (North Carolina and Wisconsin). One hundred volunteers were recruited primarily by advertisement, and participants were assigned to 666 mg (2 pills) oral acamprosate 3 times daily (1, 998 mg/d) or matching placebo over a 12‐week period. All participants concomitantly received 5 sessions of a brief behavioral intervention from a family/primary care physician. Results No significant treatment effect of acamprosate was found on PDA or the secondary outcomes. Significant treatment goal by time interaction effects was found on PDA and %HDD. Participants who had an initial goal of abstinence versus a reduction in alcohol use improved on average over time in PDA and had less %HDD from baseline to the end of treatment. Conclusions This clinical trial did not find evidence of efficacy for acamprosate compared to placebo among alcohol‐dependent individuals recruited primarily by advertisement as studied in a primary care setting. Drinking outcomes significantly improved regardless of medication condition. A goal of abstinence was significantly associated with improved drinking outcomes, suggesting that alcohol‐dependent patients with such a goal may do particularly well with counseling in a family medicine setting.